2018
DOI: 10.1016/j.idh.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical features of imported malaria at the three main hospitals of the Friuli-Venezia Giulia Region, Italy

Abstract: Background: Imported malaria cases continue to occur in non-endemic regions among travellers returning from tropical and subtropical countries. At particular risk of acquiring malaria is the group of travellers identified as immigrants who return to their home country with the specific intent of visiting friends or relatives (VFRs) and who commonly believe they are immune to malaria and fail to seek pre-travel advice. Our aim was to review the current trends of imported malaria in the three main hospitals of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…On the contrary, McLellan et al 9 performed the same type of screening in 253 HIV-positive patients but the prevalence of positive serology for Schistosoma and Strongyloides was 19.9 and 4.4%, respectively. Regarding malaria, previous studies 10 carried out in Italy found that only 15% of malaria appears in the immigrant population compared with more than 20% found in a similar Spanish study. 11 Recent recommendations on screening for Chagas in the immigrant population in Spain 12 find a prevalence mean of 6.08% but with a 95% CI between 3.24 and 9.7.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…On the contrary, McLellan et al 9 performed the same type of screening in 253 HIV-positive patients but the prevalence of positive serology for Schistosoma and Strongyloides was 19.9 and 4.4%, respectively. Regarding malaria, previous studies 10 carried out in Italy found that only 15% of malaria appears in the immigrant population compared with more than 20% found in a similar Spanish study. 11 Recent recommendations on screening for Chagas in the immigrant population in Spain 12 find a prevalence mean of 6.08% but with a 95% CI between 3.24 and 9.7.…”
Section: Introductionmentioning
confidence: 68%
“…24 From this point of view, our results show important prevalence levels for the different diseases that were included in the screening, as has been previously described. [3][4][5][6][7][8][9][10][11] Most of the current institutional recommendations have been based on the combination of the prevalence found in the immigrant population already settled in the recipient country and the prevalence in the countries of origin. These data depend mostly, on the one hand, on the national epidemiological records based in many cases on estimates made in the field or on descriptive studies published by different groups of authors from the receiving countries, in which there may be significant individual variability in the methodology, type of registry, or diagnostic protocols applied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To accelerate progression towards malaria eradication, multiple interventions are needed, but an accurate and sensitive surveillance of malaria transmission is essential to guide them [4]. On the other hand, Europe and other non-endemic countries nowadays face renovated malaria challenges; the increased influx of refugees, migrant populations, and travelers from endemic areas can contribute to the build-up of an infectious parasite reservoir, and climate change might favor mosquitos' proliferation and parasite development, further facilitating malaria transmission [5][6][7][8][9][10]. A prompt and accurate diagnosis of malaria is part of effective disease management [4,11].…”
Section: Introductionmentioning
confidence: 99%